MECHANISMS OF EFFECTIVE USE OF INNOVATIONS IN THE DEVELOPMENT OF SMALL BUSINESS ENTITIES - Rustamov Alisher Rakhmatullaevich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article presents ideas and considerations about the mechanisms of effective use of innovations in the development of small business entities.